Strategies Concerning Synergistic Development between Scientific Journals and Academic Communities - Li, Xue; Zhou, Jing; Han, Yingchun; Pei, Chu; Long, Xiufen; Li, Wushuang; Wang, Han; Li, Zehua (International Journal of Psychosocial Rehabilitation, 2024)
This research aims to undertake a comprehensive overview of how scientific journals interact with academic communities, comparing them to academic communities. This research investigated the salient features of Chinese scientific journals in relation to academic communities, , entailing a systematic approach to overseas literature review, translation, analysis, and synthesis of the attributes of academic communities. The conclusions underscore the necessity for: (1) Enhancing the formation of academic communities through the demarcation of academic resources and enhancement of dissemination frameworks; (2) Catalyzing the evolution of academic communities via the institution of governance and augmentation; (3) Amplifying the cohesive attraction of academic communities by guiding research directions and diversifying resource capabilities; (4) Elevating the impact of academic communities on scientific journals. In conclusion, global scientific journals are positioned to construct and nurture academic communities that resonate with their distinctive professional identities, thereby utilizing collective synergy to enhance the overall impact of scientific journals.